Confrontation and cooperation between timber-imitating appearance and brick masonry in the Wuliang Hall: a case study of Manjusri Hall and Samantabhadra Hall of Longchang Temple - Yukun Ma; Qing Chun (Journal of Asian Architecture and Building Engineering)
The Manjusri Hall and Samantabhadra Hall of Longchang Temple in Baohua Mountain are representative of a series of Wuliang Halls, a distinctive architectural heritage type in China. To better understand the technical and artistic characteristics of the timber imitation by bricks of the Wuliang Hall, the spatial, formal, and structural features of the two halls are analyzed. Firstly, an accurate survey of the architectural heritage is conducted to obtain precise geometric dimensions, enabling analyses of spatial and formal aspects of the hall. Subsequently, the structural performance of the hall under static load is analyzed by finite element method. The results indicate that barrel vaults and arches of different sizes serve distinct spatial functions. The appearance form of the Wuliang Hall generally aligns with the style of the Ming and Qing official timber buildings, while the detailed construction methods may be adjusted due to material or structural considerations. Vault and arch structures are employed to adapt to brick masonry, but the sill walls, tops and imposts of arches and vaults are prone to tensile damage under vertical loads or seismic actions. These results could contribute to the interpretation of the technical motivations and human ideologies for Chinese masonry timber-imitating structures, and making conservation strategies for buildings of this type.